2015
DOI: 10.1007/s00128-015-1591-8
|View full text |Cite
|
Sign up to set email alerts
|

Study on Metal Concentrations in Tissues of Mallard and Pochard from Two Major Wintering Sites in Southeastern Caspian Sea, Iran

Abstract: We examined concentrations of cadmium, chromium, iron, lead and zinc in the kidney, liver, and pectoral muscle of Mallards (Anas platyrhynchos; n = 30) and Pochards (Aythya ferina; n = 30) from two important wintering sites in the southeastern Caspian Sea in the winter of 2012. Mean lead concentrations (µg g(-1) ww) in livers (2.36 ± 1.00) of Pochard and in kidneys (3.43 ± 0.91) of Mallard exceeded the exposure threshold levels in liver (1.5 µg g(-1) ww) and kidney (3 µg g(-1) ww) of waterfowl. Mean cadmium co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 30 publications
4
14
4
Order By: Relevance
“…Cadmium concentrations that we observed in the kidneys and liver of Gadwall were higher than noted for ecologically similar species on other areas such as western Iran, southern Poland, and eastern Croatia [ 16 , 25 , 45 ]. However, even higher concentrations were reported by Hassanpour et al [ 31 ] and Sinkakarimi et al [ 55 ] in kidneys and liver of Common Coot (2.11 and 2.22 μg/g ww) and Pochard (2.16 and 1.63 μg/g ww) collected from the same wetlands as our specimens, confirming that waterbirds using Miankaleh and Gomishan International Wetlands are exposed to increased concentrations of Cd. The type of Cd exposure (i.e., acute vs. chronic) may be evaluated on the basis of the ratio of liver to kidney concentrations.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Cadmium concentrations that we observed in the kidneys and liver of Gadwall were higher than noted for ecologically similar species on other areas such as western Iran, southern Poland, and eastern Croatia [ 16 , 25 , 45 ]. However, even higher concentrations were reported by Hassanpour et al [ 31 ] and Sinkakarimi et al [ 55 ] in kidneys and liver of Common Coot (2.11 and 2.22 μg/g ww) and Pochard (2.16 and 1.63 μg/g ww) collected from the same wetlands as our specimens, confirming that waterbirds using Miankaleh and Gomishan International Wetlands are exposed to increased concentrations of Cd. The type of Cd exposure (i.e., acute vs. chronic) may be evaluated on the basis of the ratio of liver to kidney concentrations.…”
Section: Resultssupporting
confidence: 83%
“…Thus, Gadwall had greater exposure to Pb than Common Teal, and they may have ingested locally expelled Pb pellets or fishing sinkers since the concentrations we observed were higher than in other waterfowl species from Iran, Poland, Croatia, and Spain; [ 17 , 25 , 45 , 59 ]). The increased exposure to Pb particles was also suspected in other species from the same area in another study in which increased Pb concentrations were observed in livers of Pochards (2.36 μg/g) and Mallards (1.16 μg/g) [ 55 ].…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…In gadwall ( Anas strepera ) and common teals ( Anas crecca ) wintering on Miankaleh and Gomishan International Wetlands, located in the southern part of Caspian Sea (northern Iran), the concentrations of lead in the liver were 10.73 and 3.60 μg/g dw (Sinkakarimi et al 2018 ), respectively. Other studies confirm that the Caspian Sea is a highly polluted area—in the livers of mallards and common pochards ( Aythya ferina ), the concentrations of lead were 3.87 ± 1.37 μg/g dw and 7.87 ± 3.33 μg/g dw (Sinka-Karimi et al 2015 ), respectively. At the beginning of the 1990s, in Turkey, environmental contamination with lead was also relatively high.…”
Section: Resultsmentioning
confidence: 73%